Sprężysto-Plastyczne Skręcanie Wycinka Torusa - Mioduchowski, A. (Engineering Transactions, 1971)
Here a general method is presented enabling the obtainment of elasto-plastic solutions for arbitrary cross-sections of the twisted section of a torus. Solutions obtained numerically are presented for the cross-section in the form of a square. These solutions show the method of propagation of the plastic zones with increasing torque in the case of a homogeneous an inhomogeneous torus.